Do Bigger Things : a practical guide to powerful innovation in a changing world - McClure, Dan, ....-; Wilde, Jennifer, ....- (New York : Fast Company Press, 2024)
In today's changing world, where business leaders navigate industry disruption, entrepeneurs struggle to push beyond initial success, and activists tackle hard challenges like climate change, there is a need for a more powerful way to do innovation. Too many innovaters are trapped by the limits of common innovation practices. The way we've been taught to create for the past two decades is failing us. It's time for a paradigm shift. To unlock the secrets to doing bigger things, this book introduces the pioneering concept of ecosystem innovation. Drawing on their experience with a range of innovators, from Fortune Global 100 companies to local entrepreneurs in Nepal, authors Dan McClure and Jennifer Wilde present remarkable stories and actionable insights for achieving more with innovation. With this step-by-step guide, you'll acquire the big-picture mindset and capabilities you need to outmaneuver fast-moving competitors and break through the ceiling on innovation impact. Do Bigger Things offers a practical way to set bolder goals, understand harder challenges, and design more powerful solutions. Shatter the notion that game-changing endeavors are beyond your reach, your organization's capabilities, or your community's grasp. The time to do bigger things is now.
Keywords: Innovatie -- ondernemen